HABBATUS SAUDAH SEBAGAI AMELIORAN FUNGSI PANKREAS PADA MENCIT DIABETES - Retno Susilowati (lp2m-uin malang, 2006)
The aims of this study are to inventory potential of Habbatus Saudah (Nigella sativa L.) to maintain pancreas B Cells, reduced blood glucose, and increases body weight diabetic mellitus patient induced by streptozotocin (STZ). STZ as antibiotic agent has a sitotoxic effect and light carcinogenic. Injection STZ cause damages Beta cells and reduce insulin secretion. Fifteen mice 60 days old with 30-31 grams bodyweight are separate into 4 groups: Diabetic group (D), treatment group (DH), treatment control (KH) and Blanco control (K) respectively. Diabetic rats are subcutaneous injected by streptozotocin (STZ) with dose 50 mg/bw. Treatment group added habbatus saudah seed crushed 4 g/kg feed ad libitum a week after injection, for 30 days treatment. The result shows that habbatus saudah has a potential pancreas ameliorant in mice, reduce blood glucose (p 0, 01) and increase mice bodyweight (p 0, 05). Key words: Mice, Ameliorant, Diabetic, blood glucose, bodyweight, streptozotocin, Habbatus saudah, Nigella sativa L.